The impact of inter-basın water transfers on the water security of Istanbul and surrounding watersheds - Bayar, Frances Varty. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2023., 2023)
In the face of climate change, urbanization, and population growth, water provision has become critical for many cities. Istanbul, the largest city in Turkey, faces water security challenges due to its location far from major water resources, rapid urbanization, and increases in population and in- migration. Droughts in the early 1990s and mid-2000s lead decision makers to rely on large-scale interbasin water transfers (IBTs) to maintain supply. This study draws from socio-hydrology to incorporate both quantitative and qualitative analyses to understand the human-water interactions that drive water security in the region. The Natural Efficiency Index and Social Efficiency (Stress Relief Index) developed by Duan et al. (2022) are used to quantify the impact of IBTs to the water security of both Istanbul and the provinces where Istanbul’s IBTs are located, Düzce, Tekirdağ, and Kırklareli, from 2000 to 2020. Based on the indices results, transfers from the Istranca Streams in Tekirdağ, and Kırklareli are considered inefficient while the Melen transfer from Düzce is more efficient. To understand the full impacts of the IBTs to water security in the region, the indices are complemented by document analysis to understand the impacts of the IBTs to the regions’ water security using approaches from political ecology, hydrosocial, and water justice studies. The document analysis found that IBTs to Istanbul led to negative environmental and socio-economic impacts to the water-exporting regions, while increasing supply to Istanbul only accelerates the megacity’s growth, leading to increased water demand, a higher vulnerability to water-related hazards and climate change, and governance challenges through managing water over such a large area.
Keywords: Water transfer -- İstanbul.; Water-supply -- İstanbul.